SISTEM MONITORING PENGENDALI DAN PENGHITUNG WAKTU PADA DRAG RACE BERBASIS MIKROKONTROLER AT MEGA 8535 - Bangun Marhendra, Vendi; Heranurweni, Sri (Elektrika, 2017)
In a drag race, which is often held by race organizers. The process of determining the jump start and determining who crosses the first finish line still relies on human monitoring. Manually recording (stopwatch) is not enough because there are many inhibiting factors, including: operator, start theft by drivers, recording results, damage to the stopwatch and others. The drag race is often held during the day. The hot weather will cause someone to get tired quickly, in this case it is aimed at the person who is the operator who monitors the theft of the start and the operator at the finish line because the person is in the middle of a very hot track. Based on the reasons mentioned above, it is necessary to have a controller and timer system on the ATMega8535 microcontrollerbased drag race. Making this tool will facilitate the work of humans in obtaining information in the racing arena that does not allow humans to do it manually, so that accurate data is obtained.Keywords: Atmega 8535 microcontroller, jump start, stopwatch